MENGUKUR LOYALITAS PELANGGAN MELALUI RETAIL SERVICE QUALITY - YUSTINA CHRISMARDANI (Trunojoyo University of Madura, 2015)
This study aims to determine the direct effects of five variables of retail service quality (X) on customer satisfaction (Y1), the direct effect of customer satisfaction (Y1) on customer loyalty (Y2), the direct effects of five X variables on customer loyalty (Y2) and the indirect effects of five X variables on customer loyalty through customer satisfaction. The data was taken from 100 customer of Tom and Jerry store. Used path analysis, the result can be reveled as : physical aspects and policy have the direct effects of customer satisfaction, while customer satisfaction has the direct effect on customer loyalty. It means that physical aspects and policy has the indirect effects of customer loyalty through customer satisfaction. Meanwhile the other variables such as reliability, personal interaction and problem solving don’t have the direct effects of customer satisfaction, it means those variables don’t have the indirect effects of customer loyalty through customer satisfaction. Only physical aspects and reliability which have the direct effects on customer loyalty.